Answer:
Step-by-step explanation:
21
Answer:
24:8 which is also just 6:2 or 3:1
Step-by-step explanation:
There are many ways you can write this, and this is what I think hope this helps
1/6p + (-4/5) is the equivalent expression. You have to add like terms, meaning constants are added to constants, variables are added to variables, etc. the result you get from adding like variables leaves you with 1/6p + (-4/5) or 1/6p - 4/5
3∅ can be rewritten as (2∅+∅)
sin(3∅) = sin(2∅ + ∅<span>)
Opening brackets on the right hand side;
= sin2</span>∅ cos ∅ + cos2∅sin<span>∅
</span><span>This simplifies to;
= 2sin</span>∅cos^2∅ + sin∅ (1- 2sin^2∅<span>)
= sin</span>∅ (2cos^2∅ + 1 - 2sin^2∅<span>)
= sin</span>∅ (2(1 - sin^2∅) +1-2sin^2∅<span>)
= 3sin</span>∅ - 4sin^3<span>∅</span>
Answer:
yes........these all are....